(untitled) (Journal of Scientific Research, 2021)
The present study was aimed to analyze the physicochemical properties of Camelina sativa L. seed oil in order to identify its utilization as a primary feedstock for biofuel production. Efforts were also made to identify and quantify the amount of α- tocopherols in Camelina seed oil and evaluated in vitro antioxidant potential of Camelina sativa seed oil and were compared with α–tocopherol standard. Physicochemical properties such as oil yield content (36.66 %), less acid value (5.39 mg KOH/g) make it a prominent feedstock for biodiesel production. Saponification value (182.66 mg KOH/g) also makes this oil useful in soap and cosmetic industries. To check in vitro antioxidant potential of Camelina seed oil H2O2, DPPH and ABTS were used as free radical inducers. Oil showed remarkable inhibition potential of trapping these free radicals. Tocopherol content was analyzed through HPTLC. Camelina sativa seed oil was found to contain 59.34 mg/100 g of tocopherol content. It is evident from this study that Camelina oil has high antioxidant potential and there is no need to add other antioxidant substances in the products formed by using Camelina sativa seed oil.